Process of Copper Slag Reduction in an Electric Furnace and the Possibilities of Its Modelling - Radosław Zybała; Sławomir Golak; Tomasz Sak; Piotr Madej (Proceedings)
Over the past several decades, numerous studies have been published on the topic of electric furnaces used in the reduction processes used for metallic slags [...]